Early nitric oxide (NO) responses to osmotic stress in pea, Arabidopsis and wheat - Kolbert, Zsuzsanna; Sahin, Natália; Erdei, László (Acta Biologica Szegediensis, 2008)
Nitric oxide (NO) is a novel diffusible, lipophylic gas, which acts in diverse physiological processes in plants. The 4,5-diaminofluorescein diacetate (DAF-2DA)- based in vivo and in situ fluorescence method of NO detection gives an excellent opportunity to investigate the transient NO generations in plant tissues. During our work with the help of this method time-dependent kinetics of NO formation were investigated in osmotic stress treated-Pisum sativum L., Triticum aestivum L. and Arabidopsis thaliana L. roots. Osmotic stress was provoked by addition polyethylene glycol (PEG 6000) to the nutrient solution. In the case of pea plants an early phase of NO generation was distinguishable, which reached a maximum point at 24th hours after PEG treatment. This transient NO accumulation was followed by a slower but more significant NO formation. In Arabidopsis roots NO was formed already in the first 12 hours, the highest NO level was detected only 36 hours after treatment. Interestingly, in PEG-treated wheat roots the first NO peak appeared already after 1 hour treatment, which slightly moderated in the following 12 hours. In the cases of all the investigated plant species two phased NO generation was observed. The significant transient NO bursts were followed by slower NO accumulations. These early NO formations could have an important role in acclimation of plants to osmotic stress.